Does Compliance Pay? Social Standards and Firm‐Level Trade. Issue 3 (17th June 2018) - Distelhorst, Greg; Locke, Richard M.
Abstract: What is the relationship between trade and social institutions in the developing world? The research literature is conflicted: Importing firms may demand that trading partners observe higher labor and environmental standards, or they may penalize higher standards that raise costs. This study uses new data on retailers and manufacturers to analyze how firm‐level trade responds to information about social standards. Contrary to the "race to the bottom" hypothesis, it finds that retail importers reward exporters for complying with social standards. In difference‐in‐differences estimates from over 2, 000 manufacturing establishments in 36 countries, achieving compliance is associated with a 4% [1%, 7%] average increase in annual purchasing. The effect is driven largely by the apparel industry—a long‐term target of anti‐sweatshop social movements—suggesting that activist campaigns can shape patterns of global trade.